Effect of Exercise Counseling on Functional Scales Quality of Life in Women with Breast Cancer - Fatemeh Shobeyri; Azita Nikravesh; Seyedeh Zahra Masoumi; Rashid HeydariMoghadam; Monochehr Karami; Masomeh Badafreh (Journal of Education and Community Health)
Background and Objectives: Breast cancer is the most prevalent cancer and the most lethal malignancy among women in the world. Diagnosis, treatment, and treatment complications incur physical, mental and social complications, and consequently reduce the quality of life in these patients. The aim of this study was to investigate the effect of exercise counseling on functional scales in women with breast cancer. Materials & Methods: This quasi-experimental study was conducted on 60 women with breast cancer selected in cancer treatment centers in Hamadan city. Participants were randomly allocated to exercise counseling group (n=30) and control group (n=30). The intervention included two weeks of exercise counseling in the gym and eight weeks of training at home. The data were collected using a demographic questionnaire, QLQ-C30 and QLQ BR-23. Data were analyzed in SPSS.20, using &chi2 Fisher’s exact test, t-test, ANCOVA at a confidence level of p<0.05. Results: The results showed that the total score of the functional scale before the intervention was 27.19 ± 81.61 and reached 25.9 ± 91.86 after the intervention, with a statistically significant difference (P<0.05). Most changes occurred in physical functioning, emotional functioning, and body image scales. No significant difference was observed between the two groups in the following scales: cognitive function, social function, sexual function, sexual pleasure and future prospects (P>0.05). Conclusion: The functional scales of exercise counseling had a positive effect on the quality of life of women with breast cancer, and led to a significant improvement in patients. This method can be used as a part of the routine therapeutic measures for these patients.